A Breath of Fresh Air in the Fog of Antimicrobial Resistance: Inhaled Polymyxins for Gram-Negative Pneumonia - Mark Biagi; David Butler; Xing Tan; Samah Qasmieh; Eric Wenzler (MDPI AG, 2019)
Despite advancements in therapy, pneumonia remains the leading cause of death due to infectious diseases. Novel treatment strategies are desperately needed to optimize the antimicrobial therapy of patients suffering from this disease. One such strategy that has recently garnered significant attention is the use of inhaled antibiotics to rapidly achieve therapeutic concentrations directly at the site of infection. In particular, there is significant interest in the role of inhaled polymyxins for the treatment of nosocomial pneumonia, including ventilator-associated pneumonia, due to their retained activity against multi-drug resistant Gram-negative pathogens, including Acinetobacter baumannii and Pseudomonas aeruginosa. This review will provide a comprehensive overview of the pharmacokinetic/pharmacodynamic profile, clinical outcomes, safety, and potential role of inhaled polymyxins in clinical practice.